Dosimetric delivery validation of dynamically collimated pencil beam scanning proton therapy. (20th February 2023) - Nelson, Nicholas P; Culberson, Wesley S; Hyer, Daniel E; Geoghegan, Theodore J; Patwardhan, Kaustubh A; Smith, Blake R; Flynn, Ryan T; Yu, Jen; Gutiérrez, Alonso N; Hill, Patrick M
Abstract: Objective . Pencil beam scanning (PBS) proton therapy target dose conformity can be improved with energy layer-specific collimation. One such collimator is the dynamic collimation system (DCS), which consists of four nickel trimmer blades that intercept the scanning beam as it approaches the lateral extent of the target. While the dosimetric benefits of the DCS have been demonstrated through computational treatment planning studies, there has yet to be experimental verification of these benefits for composite multi-energy layer fields. The objective of this work is to dosimetrically characterize and experimentally validate the delivery of dynamically collimated proton therapy with the DCS equipped to a clinical PBS system. Approach . Optimized single field, uniform dose treatment plans for 3 × 3 × 3 cm 3 target volumes were generated using Monte Carlo dose calculations with depths ranging from 5 to 15 cm, trimmer-to-surface distances ranging from 5 to 18.15 cm, with and without a 4 cm thick polyethylene range shifter. Treatment plans were then delivered to a water phantom using a prototype DCS and an IBA dedicated nozzle system and measured with a Zebra multilayer ionization chamber, a MatriXX PT ionization chamber array, and Gafchromic™ EBT3 film. Main results . For measurements made within the SOBPs, average 2D gamma pass rates exceeded 98.5% for the MatriXX PT and 96.5% for film at the 2%/2 mm criterion across all measured uncollimated and collimated plans, respectively. For verification of the penumbra width reduction with collimation, film agreed with Monte Carlo with differences within 0.3 mm on average compared to 0.9 mm for the MatriXX PT. Significance . We have experimentally verified the delivery of DCS-collimated fields using a clinical PBS system and commonly available dosimeters and have also identified potential weaknesses for dosimeters subject to steep dose gradients.